Evaluation Of The Fitness Level Of Elementary School Students Using Vo2max Through Multi-Stage Fitness Test Methodevaluation Of The Fitness Level Of Elementary School Students Using Vo2max Through Multi-Stage Fitness Test Method - Fatah, Muhammad; Sulthon Abdillah, M. (Proceeding of International Joint Conference on UNESA, 2025)
This study evaluates the fitness level of elementary school students by measuring VO2max using the Multi-Stage Fitness Test (MFT) method. A quantitative descriptive design was used with 36 students (20 males and 16 females) participating in the fitness test. The results showed that the average VO2max for male students was 33.7 mL/kg/min, while for female students it was 28.0 mL/kg/min. Both groups were found to be below the ideal fitness category, highlighting a concerning level of physical fitness that may impact their health and cognitive development. Factors influencing fitness levels included physical activity, understanding of nutrition, and the effectiveness of physical education programs. The study underscores the need for structured, engaging physical education initiatives to increase students' participation in physical activity and potentially improve their overall fitness and health outcomes.